KEBUTUHAN BULU MERAK HIJAU (Pavo muticus muticus) UNTUK REOG PONOROGO - Widodo, Tri Wahyu; ., Gunawan; DNA, Fajar; Nursalim, Tauhid; Santoso, Basuki; Diswanto, Eggi; Kurniawan, Eddy; Hidayat, Taufiq (SIMBIOSIS, 2020)
Abstract. Reog is one of Indonesian art which is origin from Ponorogo, East Java. Barongan (dadak merak), the most dominant element of this art using the part of protected animals the green peafowl (Pavo muticus)’s feathers. In 2018, we do research to one green peafowl breeder and four “barongan” maker’s groups in Ponorogo District. Our research result found that to make single “barongan”, they need about 900-1200 feathers which is similar with 6-10 male green peafowl. Our data also shows that every groups produce about 20 “barongan” in every year. The only one green peafowl breeder in Ponorogo who has 12 adult male only can supply for one maker group. So, if we want to make reog ponorogo recognized as a world heritage, we need 20 green peafowl breeders which have 6-10 adult male individual.